An Innovative Compact Split-Ring-Resonator-Based Power Tiller Wheel-Shaped Metamaterial for Quad-Band Wireless Communication - Afsar, Md. Salah Uddin; Faruque, Mohammad Rashed Iqbal; Abdullah, Sabirin; Islam, Mohammad Tariqul; Khandaker, Mayeen Uddin *; Al-mugren, K. S. (MDPI, 2023)
A split-ring resonator (SRR)-based power tiller wheel-shaped quad-band "-negative metamaterial is presented in this research article. This is a new compact metamaterial with a high effective medium ratio (EMR) designed with three modified octagonal split-ring resonators (OSRRs). The electrical dimension of the proposed metamaterial (MM) unit cell is 00.086λ × 0.086λ, where λ is the wavelength calculated at the lowest resonance frequency of 2.35 GHz. Dielectric RT6002 materials of standard thickness (1.524 mm) were used as a substrate. Computer simulation technology (CST) Microwave Studio simulator shows four resonance peaks at 2.35, 7.72, 9.23 and 10.68 GHz with magnitudes of